Linear growth of children with celiac disease after the first two years on gluten- free diet: a controlled study - Soliman, Ashraf T; Laham, Muhannad; Jour, Celine; Shaat, Mona; Souikey, Fatima; Itani, Maya; Al-Safi, Athba; Karmallah, Alaa; Qudaisat, Anwar; Alarabi, Zohair; Hassan, Ayman; Quraan, Eyad; et al. (Acta Biomedica Atenei Parmensis, 2019)
Background: Celiac disease (CD) is a lifelong disorder with gluten-induced manifestations in different organs especially growth. Gluten free diet (GFD) is required to achieve remission and prevent abnormal growth. Study reports on growth of children with celiac disease on long-term GFD are not consistent. Objective: We evaluated the effect of GFD on growth of children with the classical form of CD (diagnosed by serology and small intestine mucosal biopsy) on log-term GFD (>2 years). Methods: We studied growth parameters (weight gain/day, BMI and BMI-SDS, height growth velocity, Ht-SDS) and lab data in 30 prepubertal children, aged 7.4±2.6 years, with CD, who were on GFD since the age of 3.2±1.6 years of age (>2 years on GFD) for duration of 1 year. The anthropometric data of 30 randomly selected normal, age and sex matched, children were used as control. Lab investigations of CD children included complete blood count (CBC), renal and liver functions (aspartate transaminase - AST, alanine aminotransferase - ALT, and alkaline phosphatase- ALP, serum albumin, fasting blood glucose, vitamin D, and thyroid function and antibodies. Results: The weight gain per day was on average or above, for age and sex, in 27 children and below average in 3. Two out of those 3 children had slow linear growth (decreased Ht-SDS by -0.56 and -0.1, over one year). BMI-SDS was normal in 26/30 patients (>-1.5). BMI-SD changed from -0.36±1.1 to -0.33±1.1 during the year of treatment. BMI-SDS decreased in 9 children during the follow up period that was explained by their fast-linear growth (increased Ht-SDS) in seven of them. The Ht-SDS was <-2 in four out of 30 children at the beginning of the study (2 years after being on GFD) and in 2 children after a year of follow-up (catch-up growth). Ht-SDS remained normal or increased in 28/30 children during the year of treatment (-0.38 ±1.2 to -0.22±1.1), with a positive trend: 0.15±0.4 SDS. Only one patient crossed down 1 Ht-SDS during the year of follow up, with low weight gain/day and decreased BMI-SDS that can be explained by poor compliance with GFD. Ht-SDS and BMI-SDS increased significantly in the CD group versus controls during the year of follow-up. All patients had normal serum albumin, liver enzyme and hemoglobin levels. 33.3% of patients had low serum ferritin level and 33.3% had a vitamin D deficiency. Conclusions: Most of our children with CD grew normally both in height and weight during GFD. Significant catch-up growth occurred in some of them after 2 years of being on GFD. Those with low BMI-SDS and/or Ht-SDS needed further management, including reinforcement on the importance of GFD and investigations on factors affecting growth pattern. Measuring weight gain /day appears to be a sensitive indicator for monitoring growth in these children. Vitamin D and iron status should be monitored, and deficiencies corrected.